Effect of Mo, Ta, V and Zr on a duplex bcc+orthorhombic refractory complex concentrated alloy using diffusion couples. (September 2020) - Lacour-Gogny-Goubert, A.; Huvelin, Z.; Perrut, M.; Boivin, D.; Horezan, N.; Guillot, I.; Vermaut, Ph.; Couzinie, J.P.
Abstract: A scanning method based on diffusion couples has been set up to experimentally explore phase diagrams and to observe the stable phases in quinary alloys. This method enables to realize a fast, experimental and reliable scanning of composition and then determine promising alloy compositions for potential structural application. Aiming at developing promising refractory complex concentrated alloys (RCCAs), the method was applied on the Ti–Nb–Al–Si system with an initial two phase, body-centered cubic (bcc) + orthorhombic (O), microstructure and focuses on the effect of Mo, Ta, V and Zr additions on this microstructure. The evolution of the orthorhombic phase fraction according to the content of additional elements was quantified, as well as the maximum concentration of those elements in order to stabilize the duplex microstructure, and maintain it above 800 °C. In such framework, it appears that Mo, Ta and V show the most promising effects on the Ti–Nb–Al–Si system. The comparisons between experimental results and calculated phase diagrams using current thermodynamic database showed that these calculations applied to RCCAs are good qualitative tools but are not accurate enough to be used as predictive means. Graphical abstract: Highlights: A scanning method based on diffusion couples is used to explore duplex BCC+O alloys in the Ti–Nb–Al–Si–X (X=Mo, Ta, V and Zr) system. Experimental results and predicted phase diagrams show qualitative agreement but significant differences regarding key features of the O phase. Mo, Ta and V appear as the most interesting addition elements for the future development of new duplex BCC+O alloys.